Behavior Disorders and Noonan's Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The behavioral phenotype and psychiatric symptoms of 21 children with Noonan's syndrome are reported from the Departments of Child and Adolescent Psychiatry, and Clinical Genetics, Royal Manchester Children's Hospital, UK.